Understanding Leisure Vacation Travel Intention of Indian Vacationers Amidst Coronavirus Disease (COVID-19) - Pandey, Kshitija; Joshi, Sujata (Indian Journal of Marketing, 2022)
This study aimed to elicit the critical factors influencing Indian domestic vacationers’ travel intention for leisure vacation destination choice amidst COVID-19. The study proposed a new model based on the theory of planned behaviour (TPB), expanding it by adding contextual variables like perceived risk, perceived knowledge of COVID-19, and information search behaviour. The study used a quantitative approach using online social media platforms and emails of 312 respondents to analyze and test the hypotheses using IBM SPSS and AMOS tools. The results indicated that physical and functional risk negatively influenced attitude; whereas, psychological risk negatively influenced travel intention. Perceived knowledge of COVID-19 significantly influenced travel intention. Attitude strongly mediated subjective norms, perceived behavioral control, and perceived knowledge of COVID-19 to travel intention. This explains the strong implications for travel destination marketers for marketing safer destination choices to vacationers.